PENGEMBANGAN E-BOOKLET TERINTEGRASI STEM PADA MATERI POLA HEREDITAS DAN EFEKTIVITASNYA TERHADAP HASIL BELAJAR KOGNITIF SISWA SMA - Tarigan, Keren Hapukh Br; Anggereini, Evita; Mardiyanti, Lely (BIOEDUKASI (Jurnal Pendidikan Biologi), 2026)
E-booklet is a teaching material that contains multimedia that presented concisely and accessible online. The purpose of this research is to determine the validity, practicality, and effectiveness of an inheritance pattern e-booklet STEM integrated. This research is a type of Research and Development (R&D) using the ASSURE model. The product trial subjects were XII F1 (8 students) and XII F2 (36 students) at SMA N 2 Kota Jambi. The data collection instruments used included expert validation questionnaires, student and teacher response questionnaires, and pretest-posttests to measure students' cognitive learning outcomes. The e-booklet was declared valid and feasible to be tested, with validation from material experts of 97% and validation from teaching material experts of 92.5%. The e-booklet was also considered practical and useful for users, with a practicality percentage of 98% from biology subject teachers, 96% from small groups, and 98% from large groups. The e-booklet effectively improved students' cognitive learning outcomes, with a Cohen d effect size of 3.36, indicating a large effect at the cognitive level of C6.Kata Kunci: Bahan Ajar, E-Booklet, Hasil Belajar Kognitif, Pola Hereditas, Research and Development, STEM